2020
DOI: 10.3762/bjoc.16.170
|View full text |Cite
|
Sign up to set email alerts
|

Naphthalene diimide–amino acid conjugates as novel fluorimetric and CD probes for differentiation between ds-DNA and ds-RNA

Abstract: Two novel unnatural amino acids, prepared by linking a dicationic purple-coloured and fluorescent naphthalene diimide (NDI) at core position to amino acid side chains of variable length, strongly interacted with ds-DNA/RNA by threading intercalation. Different from a reference NDI dye with identical visible range absorbance (520–540 nm) and Stokes shifts in emission (+60 nm, quantum yield > 0.2), only these amino acid–NDI conjugates showed selective fluorimetric response for GC-DNA in respect to AT(U)-polyn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 59 publications
0
2
0
Order By: Relevance
“…In the case of DNA-based co-assemblies, only weak induced CD (ICD) bands were observed (Figure S11a–c). This indicated that presumably only a fraction of PIm N molecules underwent intercalation or groove binding, whereas the rest of the molecules were bound as multivalent aggregates to DNA through electrostatic interactions. , Similarly, the absence of ICD in the heparin co-assembles confirmed the multivalent surface interaction of the aggregates with heparin (Figure S11d–f). Further experiments were performed to investigate the other aspects connected to the co-assembly formation.…”
Section: Resultsmentioning
confidence: 78%
See 1 more Smart Citation
“…In the case of DNA-based co-assemblies, only weak induced CD (ICD) bands were observed (Figure S11a–c). This indicated that presumably only a fraction of PIm N molecules underwent intercalation or groove binding, whereas the rest of the molecules were bound as multivalent aggregates to DNA through electrostatic interactions. , Similarly, the absence of ICD in the heparin co-assembles confirmed the multivalent surface interaction of the aggregates with heparin (Figure S11d–f). Further experiments were performed to investigate the other aspects connected to the co-assembly formation.…”
Section: Resultsmentioning
confidence: 78%
“…Herein, we chose two negatively charged biopolymers heparin and ds DNA as biomolecular scaffolds to fabricate FRET systems with multi-stimuli responsiveness. Heparin is the most negatively charged dense biopolymer and routinely used as an anticoagulant in clinical applications , whereas DNA bears the genetic information of the living systems. , In the presence of these biopolyanions, cationic pyrene appended imidazolium amphiphiles ( PIm N , N = 8, 10, and 12, the number of carbon atoms present in the attached n -alkyl segments, Figure ) which were in the self-assembled state in aqueous media and formed electrostatically driven co-assemblies (the self-assemblies are hereafter designated as SA N , whereas the heparin and DNA-based co-assemblies would be referred as HCA N and DCA N , respectively. N denotes the number of carbon atoms in the alkyl segment).…”
Section: Introductionmentioning
confidence: 99%